Reconstructive surgery of an extremely calcified mitral valve in a Barlow disease patient – a case report - Stojanović, Ivan; Kaitović, Marko; Novaković, Aleksandra; Vuković, Petar (Vojnosanitetski pregled, 2021)
Introduction. Mitral valve calcifications are frequent finding in Barlow disease. This is making mitral repair surgery even more demanding in already complex valve pathology. Case report. A fifty–five-year-old Barlow disease patient underwent a mitral repair surgery due to posterior leaflet prolapse at P2 level and extensive posterior leaflet and annular calcifications as well. The prolapsed scallop was resected, while P1 and P3 scallops were detached from the annulus. After complete posterior annulus decalcification, so formed the large atrio-ventricular defect was reconstructed with the autologous pericardial patch and double suture line technique. The P1 and P3 segments were reattached there by the sliding technique and sutured with no strain. Annuloplasty was performed with a saddle rigid ring No 36. The patient was discharged nine days after the surgery with just a trace of mitral regurgitation. Conclusion. Annular decalcification and reconstruction in the patients with calcified Barlow mitral disease is neccessary for safe and durable mitral valve surgical repair.